Design of a Closed Air Open Water Humidification Dehumidification Desalination System - S Bhardwaj, Haresh; A R, Sreenath; Raj P, Ranjitha; J S, Jayakumar; P C, Sreekumar; Shankar, Balakrishnan (International Journal of Engineering and Technology, 2018)
Desalination is the processes used to generate pure water from seawater. Humidification-Dehumidification (HDH) desalination is a low temperature thermal desalination process where the required thermal energy can be obtained from low quality sources. This paper details the design, analysis and fabrication of a Closed Air Open Water (CAOW), Saline Water Heated HDH equipment, capable of producing 50 litres of water in 6 hours. The main components, i.e. the humidifier, water heating chamber and dehumidifier were constructed from SS 3048 in order to resist corrosion. Multiple designs for sparger were considered, and keeping in mind the pressure drop experienced by the air, spider type spargers were chosen.  The equipment is capable of studying the effect of operating parameters, such as liquid column height, superficial gas velocity, etc. on dehumidifier and humidifier effectiveness.  It is also proposed to use different carrier gases in place of air, and a mechanism consisting of multiple valve-pipe arrangement was designed and fabricated in order to facilitate removal and filling of carrier gas in the equipment.